Wet-priming extracorporeal membrane oxygenation device maintains sterility for up to 35 days of follow-up. (May 2013) - Naso, F; Gandaglia, A; Balboni, P; Zanella, F; Danesin, R; Spina, M; Gerosa, G
In emergency cases, rapid extracorporeal membrane oxygenation (ECMO) device initialization is able to drastically reduce the incidence of patient morbidity and/or mortality. Pre-assembled and ready-to-use ECMO circuits might save up to 30-60 critical minutes in patient management. Six ECMO circuits (Oxygenator D905 EOS with REVOLUTION™ pump and Sorin PTS) were assembled in the operating room in standard conditions and then placed at 37°C for 35 days in order to evaluate possible contamination and ingrowth of micro-organisms. Every 7 days after ECMO circuit assembly and wet-priming, samples of priming fluid were analyzed to verify the presence/absence of possible common contaminants ( Enterobacteriaceae, Staphylococcus aureus and fungi). Moreover, two supplementary circuits, used as positive controls, were deliberately inoculated with a known concentration of a Escherichia coli strain and prime samplings carried out at different time-points to determine bacterial growth rate. Sterility was maintained in the ECMO circuits for up to 35 days.